Increasing the added value of bananas through product diversification into plantain flour and innovative coffee in Blitar - Juwita, Ratna; Manggara, Algafari Bakti; Angelica, Yohana Claudia; Rosari, Gisella Merischa; Fatin, Adhwa Dhawiya; Gunawan, Pristiko (Community Empowerment, 2025)
Kepanjenlor Village, Blitar City, has abundant agricultural potential in bananas, which are relatively inexpensive and non-seasonal. This condition necessitates innovation to increase the added value of bananas to build economic independence. This community service activity aimed to create new business opportunities for the women of the Family Welfare Empowerment (PKK) program through training in diversified banana processing. The method applied was training and mentoring using appropriate, functional food-based technology. The training covered processing banana fruit into plantain flour as a wheat alternative, and processing banana peels into innovative coffee powder. Evaluation results showed a significant improvement in participants' skills, with 90% of participants succeeding in making plantain flour and 85% succeeding in making the coffee powder. This training proved effective in enhancing the skills and potential for economic independence within the community through functional food products based on local resources.